A dieta das larvas de Mylossoma aureum e M. duriventre na Amazônia central - Leite, Rosseval Galdino; Araujo-Lima, Carlos A. R. M. (Acta Amazonica, 2000)
Mylossoma aureum and M. duriventre are two abundant species in the Amazon floodplain, but little is known about their larval ecology. Here, it is described the diet of 4,5 to 16mm long larvae sampled in the river and in five lakes along the Amazon. The larvae were caught with ichthyoplankton net and hand net in the main mesohabitats of the river and flood-plain. The stomach content of both species were analyzed by lake and larval size, and the contribution of the food particles accessed by their dry weight (µg). It was found that the fish fed primarily under the floating grass mats and rarely in river mesohabitats. The foremost food of both species were, initially, ciclopoid copepods and later chironomid larva. The main sources of variation in the proportion of food items in the diets were the lakes and larval length. Both species consumed particles smaller than 50% of their mouth gap. Great lenght food ingestion result in smaller amount of preys in the larva alimentary tract.
The larval diet of Mylossoma aureum and M. duriventre in Central Amazon
Keywords: Fish; Feeding; Larvae; Amazon; Zooplankton; Peixe; Alimentação; Larva; Amazônia; Zooplâncton